Complexos de rutênio (II) de interesse biológico: avaliação in vitro e in vivo do potencial antitumoral e genotóxico - Souza, Andréa Prado Carnizello (2014)
This work evaluated ruthenium (II) complexes in biological assays in vitro on tumor cells and non-tumor, and in vivo in male Swiss and C57BL/6 mice, as well as the interactions with DNA and BSA were evaluated. The compounds (1) [Ru(dppb)(SpyMe2-N,S)2]; (2) [RuCl (SpyMe2-N,S)2NO]; (3) [Ru(Pic)2(dppb)]; (4) [Ru(Gly)(dppb)(4,4'-mebipy)]PF6; (5) [Ru(Gly)(dppb)(phen)]PF6; (6) [Ru(Tyr)(dppb)(4,4'-mebipy)]PF6; (7) [Ru(Tyr)(dppb)(phen)] PF6; (8) [Ru(Trp) (dppb)(phen)]PF6 and (9) ct-[RuCl(CO)(dppb)(bipy) ]PF6 (where, dppb = 1,4-bis (diphenylphosphino) butane; pic = picolinate; SpyMe2 = 4,6-dimethyl-2- mercaptopyrimidine, 4,4'-mebipy = 4,4'-dimethyl-2, 2'-bipyridine; phen = phenanthroline; Gly = glycine, Tyr = tyrosine, Trp = tryptophan; bipy = 2,2'- bipyridine) underwent a screening evaluation of cytotoxic activity on different tumor cell lines U251, HeLa, MCF7, HepG2 , MO59J and B16F10 and non tumour V79, in different concentrations by XTT method. The compound 9 was selected for the assessment of interactions with DNA and BSA, the genotoxic potential in vitro (V79 and HepG2 cells), in vivo (Swiss mice), as well as to evaluate the antitumor potential in vivo (C57BL/6 mice). In vitro experiments, the compoud 9 was assessed at various concentrations in the tests of interactions with DNA and BSA and micronucleus test. In vivo experiments, animals were treated with different doses of the compound 9 by intraperitoneal route in the micronucleus and comet assays, and subcutaneous route in the evaluating of the antitumoral potential. The micronucleus test in bone marrow and comet in hepatocytes were employed to study the potential genotoxic. For both assays, in vitro and in vivo, groups negative controls (water) and positive (methyl methanesulfonate and cisplatin) were included. The results of in vitro cytotoxicity assays showed that the HeLa and MCF7 tumor cells were sensitive to the majority of the complexes evaluated. However, the compound 9 showed cytotoxicity against all tumor cell lines evaluated, with low IC50 values. In the experiments of interaction with DNA and BSA, the compound 9 showed weak interactions with DNA and hydrophobic interactions for BSA. The results obtained in vitro micronucleus tests for complex 9 showed absence of genotoxicity in V79 cells and in HepG2 tumor cells showed up genotoxic at a concentration of 1.25 μmol L-1. In experiments in vivo micronucleus, the compound 9 was not genotoxic in different doses evaluated. Regarding the comet assay, the results showed an increased frequency of DNA damage in hepatocytes in a dose of 5.0 mg kg-1 b.w. In vivo antitumor test, animals treated with 5.0 mg kg-1 b.w. of compound 9, showed significant inhibition of tumor growth compared to untreated control. In the histopathological analysis, the compound 9 also showed significant inhibition of mitosis in relation to the control group. Most of the compounds evaluated in this study showed in vitro cytotoxic activity on tumor cells, especially in MCF7 cells. The compound 9 showed promising results in biological in vitro and in vivo assays, suggesting that this compound may be potential candidate for chemotherapy in cancer treatment.